Способ получения окисленного изотактического полипропилена - Нехорошев С. В. Сергей Викторович; Дахновская Е. В. Евгения Викторовна; Нехорошева А. В. Александра Викторовна; Кузьменко О. С. Олег Степанович; Нехорошев В. П. Виктор Петрович; Слепченко Г. Б. Галина Борисовна
опубл. 27.02.16